Impact of Particulate Matter on Hospitalizations for Respiratory Diseases and Related Economic Losses in Wuhan, China - Qin, Guiyu; Wang, Xuyan; Wang, Tong; Nie, Dewei; Li, Yanbing; Liu, Yan; Wen, Haoyu; Huang, Lihong; Yu, Chuanhua (Frontiers in Public Health, 2022)
Background: Prior studies have reported the effects of ambient particulate matter (APM) on respiratory diseases (RD) hospitalizations, but few have quantified APM-related economic loss, especially in heavily polluted metropolises in developing countries. This investigation aimed to assess the impacts of APM pollution on the risk burden and economic loss of RD admission patients. Methods: Daily cases of RD hospital admission from January 1, 2015 to December 31, 2019 were collected from two Third-level Grade A hospitals in Wuhan, China. Time-series analysis incorporated with generalized additive model was adopted to assess the impacts of PM2.5 and PM10 exposure on RD hospitalizations. Stratified analyses were performed to investigate underlying effect modification of RD risk by sex, age, and season. The cost of illness approach (COI) was applied to evaluate the related economic losses caused by APM. Results: A total of 45699 inpatients with primary diagnosis of RD were included for analysis. PM2.5 and PM10 exposures were associated with increased risks of hospitalizations for RD. Subgroup analysis demonstrated that the males and the 0–14 years old group were more vulnerable to APM and the adverse effects were promoted by low temperature in cold season. A 196 million Chinese Yuan economic loss could be avoided if concentrations of PM2.5 and PM10 declined to 10 μg/m3 and 20 μg/m3 respectively. Conclusions: PM2.5 and PM10 concentrations were positively associated with RD hospitalization. Males and children were more vulnerable to APM. Effective air pollution control measures can reduce hospitalizations significantly and save economic loss substantially.